2018
DOI: 10.7717/peerj.5521
|View full text |Cite
|
Sign up to set email alerts
|

Detection and phylogenetic analysis of adenoviruses occurring in a single anole species

Abstract: Adenoviruses (AdVs) infect a wide range of hosts, and they have undergone recent and ancient host transfers multiple times. In reptiles, AdVs have been found in many captive individuals, and have been implicated in morbidity and mortality in several species. Yet the pathogenicity, transmission, phylogenetic distribution, and source of AdVs in the environment are still unknown. We therefore chose to opportunistically sample deceased captive Anolis sagrei individuals that were collected from different population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…To that end, we present the largest, comprehensive, phylogenetic analysis performed to date of HAdVs and SAdVs circulating worldwide. The trees in this study are very similar to those constructed previously both as preliminary trials and in other studies reported, albeit in small-scale datasets and recovered using different phylogenetic methods (Prado-Irwin et al, 2018;Harrach et al, 2019), with some minor changes in tree topology that do not affect our major conclusions. This larger phylogenomic study of the primate adenoviruses, particularly of 174 whole genomes, allows a more precise and comprehensive understanding of the evolutionary relationship of human and simian adenoviruses.…”
Section: Discussionsupporting
confidence: 84%
“…To that end, we present the largest, comprehensive, phylogenetic analysis performed to date of HAdVs and SAdVs circulating worldwide. The trees in this study are very similar to those constructed previously both as preliminary trials and in other studies reported, albeit in small-scale datasets and recovered using different phylogenetic methods (Prado-Irwin et al, 2018;Harrach et al, 2019), with some minor changes in tree topology that do not affect our major conclusions. This larger phylogenomic study of the primate adenoviruses, particularly of 174 whole genomes, allows a more precise and comprehensive understanding of the evolutionary relationship of human and simian adenoviruses.…”
Section: Discussionsupporting
confidence: 84%
“…The newly discovered hosts include, among others, Mexican beaded lizard and gila, from each of which an isolated strain was obtained as well. From free‐living individuals, bearded dragons, anole lizards, and worm lizards, more reliable data can be deduced, which usually confirm a link between a certain host species and AdV type . The full genome of lizard AdV‐2, isolated from Mexican beaded lizard, was determined and the structure of the virion was also studied.…”
Section: Advs In Squamate Reptiles (Atadenovirus)mentioning
confidence: 99%
“…Most of the previously published phylogenies of the family Adenoviridae were obtained using the single-locus approach. To construct a phylogenetic tree, the alignment of the sequences of individual genes or proteins encoded by them, in particular, DNA-dependent DNA polymerase [1, [73][74][75], hexon [4,[76][77][78], penton base, or fiber-2 [59] is traditionally used.…”
Section: Discussionmentioning
confidence: 99%